(untitled) (Revista Ciencia Agraria, 2025)
Given the increasing sophistication of tourism demand, understanding the expectations of the modern traveler is crucial to ensuring sustainability and commercial success in the sector. The objective of the article was to identify the main satisfaction factors of tourists in luxury hotels through a literature review. The study adopted a qualitative, review-based approach using the PRISMA systematic review methodology; the search considered only scientific articles in Spanish, English, and Portuguese published between 2005 and 2025 in the Scielo and Scopus databases, using the Boolean operators ((satisfaction AND hotel AND luxury AND tourism)), resulting in the selection of 10 articles for the final review. The results indicate that while guest satisfaction in luxury hotels is based on a balance between human interaction, physical comfort, and the overall quality of the experience, staff attention is the most valued factor. It is possible to conclude that satisfaction is a multidimensional process and component where both physical and abstract aspects reinforce each other; to integrate a solid service culture with adaptive strategies, luxury hotels must generate lasting bonds, regardless of the market segment being targeted.